Rechargeable iron / Nur Khalidah Yahaya and Intan Syafiqah Mohamad Fauzi - Yahaya, Nur Khalidah; Mohamad Fauzi, Intan Syafiqah (2016)
Our project is rechargeable iron. Rechargeable iron is a wireless iron. Users only need to charge the iron and when charging is completed, the user just needs to iron the clothes as usual and the user does not have to worry about the power source. It is also a small size iron as the palm of the hand and users can bring together anywhere on vacation or office due to its small size and mobile. Two in one package. Besides functioning as a clothes iron, it also functions as a hair iron.